rs2572431 Polymorphism on Chromosome 8 Is Associated With Individual Differences in Anxiety Related Coping Modes - Jung, Sonja; Sindermann, Cornelia; Lachmann, Bernd; Montag, Christian (Frontiers in Psychology, 2019)
Objective: The role of genetic factors in the interplay between anxiety-related coping and personality has been the subject of interest in numerous previous studies. The current study focused on anxiety-related coping modes, namely repression versus sensitization (i.e. cognitive avoidance versus vigilance), and the single nucleotide polymorphism (SNP) rs2572431. An association between this SNP and personality has previously been shown in a genome wide association study, thus further investigation of the relationship between this SNP and anxiety-related coping seems warranted. Method: In the present study, N =880 mostly Caucasian participants (n = 269 males and n = 611 females; mean-age: 23.88; SD = 7.19) filled in a personality questionnaire assessing individual differences in cognitive avoidance and vigilance, and all participants were genotyped for rs2572431. Results: Participants homogenous for the T-allele in rs2572431 showed the highest vigilance scores in all scenarios tested. This is in line with findings from an earlier genome wide association study demonstrating that the TT variant is also associated with higher neuroticism scores. Conclusion: The current study yields evidence for the role of rs2572431 in the molecular genetic underpinnings of coping behaviour and, more broadly, for its connection with personality.